Evaluasi Kebijakan Pengelolaan Persampahan di Kabupaten Purwakarta - R Dadan Suwandana; Endang Wirjatmi Tri Lestari; Nita Nurliawati (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2022)
The purpose of the research is to evaluate and develop recommendations for waste management policies based on evaluation criteria such as Effectiveness, Efficiency, Adequacy, Equity, Responsiveness and Accuracy of the object of research at the Environmental Service of Purwakarta Regency. This type of research is a qualitative research with data collection techniques consisting of observations, interviews and primary data. While the technical analysis by means of data reduction, data presentation, drawing conclusions. The results show that the waste management policy has been implemented but has not been running well because there are still problems in the evaluation criteria such as effectiveness, adequacy, responsiveness and accuracy. Meanwhile, the criteria for efficiency and equity are sufficient.